2013
DOI: 10.3389/fnhum.2013.00406
|View full text |Cite
|
Sign up to set email alerts
|

Unfair offers, unfair offenders? Fairness considerations in incarcerated individuals with and without psychopathy

Abstract: Offenders with psychopathy have often committed crimes violating social norms, which may suggest a biased moral reasoning in psychopathy. Yet, as findings on utilitarian decisions remain conflicting, the current study investigated different aspects of fairness considerations in offenders with psychopathy, offenders without psychopathy and healthy individuals (N = 18/14/18, respectively). Unfair offers in a modified Ultimatum Game (UG) were paired with different unselected alternatives, thereby establishing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…In addition, the EPT results revealed that AOs had no difficulties to judge the correctness of actions performed by the perpetrator or the punishment deserved. This finding is consistent with previous evidence for adequate moral judgment in offenders ( Cima et al, 2010 ; Schmoll, 2012 ; Radke et al, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the EPT results revealed that AOs had no difficulties to judge the correctness of actions performed by the perpetrator or the punishment deserved. This finding is consistent with previous evidence for adequate moral judgment in offenders ( Cima et al, 2010 ; Schmoll, 2012 ; Radke et al, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results may thus indicate that AVOs' decisions were rather rational, as they continued to pursue their rational strategy of profit maximization irrespective of whether the offer was made by a social or non-social proposer. Only one previous study directly compared differences between social vs. non-social proposers on gambling behavior in psychopathic offenders and reported differences in the behavioral adjustment to social context variables between psychopathic offenders, non-psychopathic offenders, and healthy controls [12]. Our findings of strategic behavior during different game settings in antisocial individuals are in line with results in healthy individuals indicating that psychopathic traits, such as Machiavellianism [47,6] and coldheartedness [5], are predictive of less emotional and more rational decision-making behavior.…”
Section: Behavioral Resultsmentioning
confidence: 99%
“…In contrast, a previous investigation in a community sample reported increased acceptance rates following unfair offers in individuals with high psychopathic traits [13] which points to an insensitivity to unfairness in high psychopathy scorers, whereas another community sampled study found no group differences [14]. The only prior study that manipulated the context (i.e., compared offers generated by a computer with offers made by another human) reported differences in the behavioral adjustment to social context variables between psychopathic offenders, non-psychopathic offenders, and healthy controls [12].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Participants are more likely to reject an unfair offer if the partner could have offered a fair allocation, but the magnitude of this effect is reduced in delinquents/offenders. 7,8 Another UG variant involves participants choosing whether to “punish” the partner by spending money to remove the partner’s money. Such behaviors expressed in this variant model retaliatory behavior in participants.…”
mentioning
confidence: 99%